Statistical analysis of EBSD data confirms pronounced classical and non-classical pervasive crystallographic twinning in rotaliid foraminiferal calcite - Wolfgang W. Schmahl; X. Yin; J. Lastam; E. Griesshaber; S. Hoerl; E. Sturm; A. Sancho Vaquer (Scientific Reports)
Abstract We describe a quantitative statistical and geometric analysis of classical and non-classical modes of twinning in the calcite produced by biomineralization in the shell of the rotaliid foraminifer species Amphistegina lessonii. Foraminifera are responsible for about a quarter of the marine production of CaCO3 and thus play a major role in the natural CO2 sequestration into marine carbonate sediments. The shell calcite of rotaliid foraminifera is nano-twinned and thus quite distinct from inorganic calcite and from biogenic calcite produced by other groups of organisms. Previous work showed that foraminiferal calcite contains a high spatial density of twin walls of the classical 60°|<001> = m.{001} twin, but there was another peak in the range between 75° and 80° in the misorientation statistics of electron backscatter diffraction (EBSD) maps of the same specimen. We checked the significance of all maxima in misorientation by in-depth statistical analysis, thus confirmed the 60°|<001> penetration twinning and found that the 75°–80° maxima are related to new, non-classical, but systematically reoccurring oriented associations of calcite crystals with orientation relationships 78.2°|<991> and 76.6°|<6 −6 1>. If the nano-twinning provides an evolutionary advantage, it may increase the strength and toughness of the feeble mineralized chamber walls of the organisms.